2015
DOI: 10.1002/2014jd023023
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐frequency radar Doppler spectral retrieval of rain drop size distributions and entangled dynamics variables

Abstract: A novel technique based on K a -W band dual-wavelength Doppler spectra has been developed for the simultaneous retrieval of binned rain drop size distributions (DSD) and air state parameters like vertical wind and air broadening caused by turbulence and wind shear. The rationale underpinning the method consists in exploiting the peculiar features observed in Doppler spectra caused by the wavelength dependence of scattering and absorption properties. A notional study based on a large data set of DSDs measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 42 publications
1
64
0
Order By: Relevance
“…This is confirmed by the air broadening (Figure b) which reaches maximum values at those levels. Air broadening is minimal in the other regions, thus signaling low turbulence conditions which are ideal for the applicability of the retrieval [ Tridon and Battaglia , ]. Similarly, integrated two‐way attenuations (Figure c) always exceed 4–5 dB, i.e., which has been found to be the threshold value for the applicability of the methodology [ Tridon et al , ].…”
Section: Strong Evaporation Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This is confirmed by the air broadening (Figure b) which reaches maximum values at those levels. Air broadening is minimal in the other regions, thus signaling low turbulence conditions which are ideal for the applicability of the retrieval [ Tridon and Battaglia , ]. Similarly, integrated two‐way attenuations (Figure c) always exceed 4–5 dB, i.e., which has been found to be the threshold value for the applicability of the methodology [ Tridon et al , ].…”
Section: Strong Evaporation Case Studymentioning
confidence: 99%
“…By using the raindrops fall speed v(D,z)=vt(D,z)w(z) where v t is the terminal fall speed corrected for air density (see equation (3) in Tridon and Battaglia [] which is based on Atlas et al [] and Frisch et al []) and w is the vertical wind speed (defined positive upward), the differential equation with respect to time can be converted into a differential equation with respect to height, z , measured downward from a given level v(D,z)2.05482ptD2.05482ptdDdz=4(RH/100)1FK+FD or equivalently dm(D,z)dt=v(D,z)2.05482ptdm(D,z)dz=2πρL2.05482ptD(RH/100)1FK+FD which provides the mass evaporation rate of the drop ( ρ L =10 3 kg m −3 is the density of water).…”
Section: Strong Evaporation Case Studymentioning
confidence: 99%
“…For this purpose, we plan to use dual-frequency wind profilers (see for instance Williams, 2012, which retrieves vertical wind in rain from two profilers). Another possibility would be to use the methods developed by Giangrande et al (2010) or Tridon and Battaglia (2015), which retrieve vertical winds and DSD from K band and/or W band Doppler spectra. We could also study the impact on the quality of the retrievals of the addition of other frequencies directly in the assimilation process.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the cases used in this study shows that the DSR plateau extends up to velocities of 2.5–3.5 m/s and 4–5 m/s for Ka/W and X/Ka spectral ratios, respectively; see Figures d and e for an example. Tridon and Battaglia () have shown that the spectral broadening, due to air motion, could affect the Rayleigh plateau and bias the DSR measurements. To mitigate this, the optimal estimation method has been utilized (Tridon et al, ; Tridon et al, ; Tridon & Battaglia, ).…”
Section: Methodsmentioning
confidence: 99%
“…Tridon and Battaglia () have shown that the spectral broadening, due to air motion, could affect the Rayleigh plateau and bias the DSR measurements. To mitigate this, the optimal estimation method has been utilized (Tridon et al, ; Tridon et al, ; Tridon & Battaglia, ). After inspecting the cases analyzed in this paper (see the list in the supporting information), we found that the DSR in the Rayleigh region is rather flat and does not seem to be affected by the spectral broadening, which would skew the plateau (Tridon et al, ).…”
Section: Methodsmentioning
confidence: 99%